Black managers in a white world: Strategy formulation - Linda Human; Karl Hofmeyr (South African Journal of Business Management, 1984)
This article takes a look not only at the strategies which could be employed towards the solution of the problems faced by both the black manager and his employing organization, but also at the possibility of providing a tentative formula for decisions relating to the amount of time, money and effort which should be expended on efforts to ameliorate problems of this kind. It is argued that attempts to successfully introduce black managers into an erstwhile 'white' world will require a combined socio-economic method of decision-making. In other words, it would appear that, in the majority of organizations which are attempting to integrate black managers into their managerial structures, it is necessary to devote resources to the partial resolution of conflict whilst at the same time not detracting from goal achievement aims. It is further argued that short-run resource allocation with regard to social versus economic ends should be based on a comparison of the relative equilibrium or growth conditions in the economic and social systems within the organization. In the long-run, a second principle - which involves working towards a reduction of the conflict between efficiency and psychological well-being and which generally involves the adaptation of the social system to the requirements of efficiency - has also to be introduced. With respect to the black manager in a white world, a number of strategies relating to manpower planning. the identification of management potential and training needs, the job itself, education and training, the organization and the total environment are put forward. All of these strategies could assist in alleviating the strains and pressures faced by both the black manager and the employing organization whilst at the same time leading in the direction of greater efficiency and possibly increased profitability.
Keywords: 650